Using Participatory Research to Develop a Culturally Responsive Early Childhood Assessment Tool - Hattie Harvey; Jennifer Pierce; Diane Hirshberg (Journal of Participatory Research Methods)
Early childhood educators are uniquely positioned to advance equity by providing culturally-responsive early learning environments and developing respectful and reciprocal relationships with families. Culturally-responsive teaching practices recognize the diverse cultures of children and families as strengths and empower children through cultural values of their family heritage (Gay, 2010). One early childhood program serving Alaska Native and American Indian (AN/AI) children and families identified a need to more systematically support educators' reflection on their knowledge, skills, and abilities related to cultural programming. This paper aims to describe the process of and lessons learned from using a participatory, community-based research approach to develop a culturally-responsive early childhood assessment tool. Operating from a postmodern/transformative paradigm, we describe the journey of this process with particular attention to shifting power to the community participants and carefully attending to our own reflexivity as three white researchers collaborating with a tribal non-profit organization.